Plastic scintillator enriched Gd-containing nanoparticles - Svidlo, O.V.; Zhmurin, P.N.; Gurkalenko, Yu.A. (Functional Materials, 2014)
Polystyrene compositions containing GdF₃ nanoparticles stabilized by ammonium di-hexadecyldithiophosphate and fatty aromatic phosphonic acid (C₆H₅-(CH₂)n-PO(OH)₂, n = 1, 2, 3) were obtained. It was shown that the nanoparticles surface modification by fatty aromatic phosphonic acids with high physical-chemical affinity to polystyrene significantly improves the nanoparticles dispersibility in polymer. The plastic scintillators with content of GdF₃ nanoparticles to 5 wt. % without significant loss of the light yield were obtained.